Crude Oil Analyses of the Yamama Formation in the Subbah, Ratawi, Tuba and Luhis Oil Fields, Southern Iraq - .Al-Ibrahim, Rafid .N; K. Al-Ameri, Thamer. (Iraqi Journal of Science, 2023)
It is evident from this study that Yamama Formation is reservoir rocks and source rocks at the same time, based on occurrences of crude oil and source rocks. Bulk properties of Yamama oil in six wells as well as comparing several samples of Yamama oil by using the biological mark have indicated multi source of hydrocarbons with some pay having Jurassic and Lower Cretaceouse source affinity that belongs to the Yamama Formation.